An analysis of ammonia synthesis by the model of Selective Energy Transfer (SET) - Larsson, Ragnar (Annals of Mathematics and Physics, 2019)
The SET theory implies that energy is transferred from the catalyst system via infrared radiation to the molecules that are supposed to react. In previous investigations it has been demonstrated that the activation of the reacting species-as long as the molecules are infrared active-can occur at low adsorption strength. However, for molecules that are IR inactive, e.g. dinitrogen, this is not possible. Hence the N2 molecule has to be adsorbed on the catalyst surface to give rise to vibrations that can interact with IR quanta of the catalyst. By analyzing the activation energies for a series of reactions between hydrogen and nitrogen under slightly differing conditions this critical vibration has been found at wave numbers such as 374, 374 and 355cm-1. The critical vibration is identified as the degenerate bending vibration of the M-N-N unit. When this bending is activated, the N2 triple bond is weakened and makes place for hydrogen addition. Two different routes of reaction are scheduled, of which one is the most likely one, using the metal-atomic nitrogen stretch vibration as the catalyst vibrator. For the classical Fe3O4 a perfect resonance (1:1) with the above-mentioned critical vibrations exist. This is also the case for the catalyst from Co3Mo3N, where a surface cover of, inter alia, MoO42- seem to act likewise in full resonance.